Stimulated Respiration and Net Photosynthesis in Cassiopeia sp. during Glucose Enrichment Suggests in hospite CO2 Limitation of Algal Endosymbionts - Rädecker, Nils; Pogoreutz, Claudia; Wild, Christian; Voolstra, Christian R. (Frontiers in Marine Science, 2017)
The endosymbiosis between cnidarians and dinoflagellates of the genus Symbiodinium is key to the high productivity of tropical coral reefs. In this endosymbiosis, Symbiodinium translocate most of their photosynthates to their animal host in exchange for inorganic nutrients. Among these, carbon dioxide (CO2) derived from host respiration helps to meet the carbon requirements to sustain photosynthesis of the dinoflagellates. Nonetheless, recent studies suggest that productivity in symbiotic cnidarians such as corals is CO2-limited. Here we show that glucose enrichment stimulates respiration and gross photosynthesis rates by 80 and 140%, respectively, in the symbiotic upside-down jellyfish Cassiopeia sp. from the Central Red Sea. Our findings show that glucose was rapidly consumed and respired within the Cassiopeia sp. holobiont. The resulting increase of CO2 availability in hospite in turn likely stimulated photosynthesis in Symbiodinium. Hence, the increase of photosynthesis under these conditions suggests that CO2 limitation of Symbiodinium is a common feature of stable cnidarian holobionts and that the stimulation of holobiont metabolism may attenuate this CO2 limitation.